Fluid and Electrolyte Disorders (IntechOpen, 2023)
This book provides readers with all the tools needed to handle interesting clinical challenges in the field of fluid and electrolyte disorders. It aims to offer an up-to-date clinical text for medical residents, fellows, practicing physicians, and nephrologists in a simple and easy-to-understand format. It provides the right balance between basic science and practical clinical guidance. It discusses the current evidence regarding the physiology, basic fundamentals, clinical presentation, and management of these disorders and will help clinicians to handle these disorders effectively. And all chapters have been extensively revised and bound to include the latest developments in the field.